Comparison of Deep Learning Techniques to Model Connections Between Solar Wind and Ground Magnetic Perturbations - Keesee, Amy M.; Pinto, Victor; Coughlan, Michael; Lennox, Connor; Mahmud, Md Shaad; Connor, Hyunju K. (Frontiers in Astronomy and Space Sciences, 2020)
Geomagnetically induced currents (GIC) can drive power outages and damage power grid components while also affecting pipelines and train systems. Developing the ability to predict local GICs is important to protecting infrastructure and limiting the impact of geomagnetic storms on public safety and the economy. While GIC data is not readily available, variations in the magnetic field, dB=dt, measured by ground magnetometers can be used as a proxy for GICs.We are developing a set of neural networks to predict the horizontal component of the magnetic field, BH, from which dBH=dt is calculated. We apply two techniques for time series analysis to study the connection of solar wind and interplanetary magnetic field properties obtained from the OMNI dataset to the ground magnetic field perturbations. The analysis techniques include a feed-forward artificial neural network (ANN) and a long-short term memory (LSTM) neural network. Here we present a comparison of both models performance when predicting the BH component of the Ottawa (OTT) ground magnetometer for the year 2011 and 2015 and then when attempting to reconstruct the time series of BH for two geomagnetic storms that occurred on 5 August 2011 and 17 March 2015.